Decision Support System: Mental Health Assessment of UTHM Students - Wan Hazemin, Wan Nurain Natasha; Salamat, Dr. Mohamad Aizi (Applied Information Technology And Computer Science, 2022)
Decision Support System: UTHM Student Mental Health Assessment is a web -based system that works to measure the level of mental health of students at Universiti Tun Hussein Onn Malaysia (UTHM). This system aims to improve the existing system at the UTHM Counseling Center which only uses a manual system to measure the level of mental health of students. UTHM Counseling Center only uses forms to analyze the level of mental health of students. This conventional method is seen as less efficient in handling data and analysis because usually mental health results are only analyzed through paper or form only. This condition will cause data loss. A prototype model was used to develop this project. While system development is realized by using Sublime software and MySQL database. The programming languages ​​used are Hypertext Preprocessor (PHP) and Hypertext Mark Up Language (HTML). The target users of the system consist of two main groups, namely administrators and users. The administrator is from the UTHM Counseling Center, while the user is a student from Universiti Tun Hussein Onn Malaysia (UTHM). The system will be developed for users to know their mental health and whether they belong to the category of mental illness such as depression, anxiety and stress based on the answers to the questions given. The system should be able to provide information on mental health and mental illness to students. The system can store user or student data. The system can generate statistical reports of students involved with mental problems based on faculty. The system also has an interaction platform between administrators and users. It is hoped that the system developed can provide facilities and benefits to students and administrators from the UTHM Counseling Center by only using the system to access data and analyze assessments.